2013
DOI: 10.3390/ijms14059168
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Aerial Part of Lindera akoensis on Lipopolysaccharides (LPS)-Induced Nitric Oxide Production in RAW264.7 Cells

Abstract: Four new secondary metabolites, 3α-((E)-Dodec-1-enyl)-4β-hydroxy-5β-methyldihydrofuran-2-one (1), linderinol (6), 4′-O-methylkaempferol 3-O-α-l-(4″-E-p-coumaroyl)rhamnoside (11) and kaempferol 3-O-α-l-(4″-Z-p-coumaroyl) rhamnoside (12) with eleven known compounds—3-epilistenolide D1 (2), 3-epilistenolide D2 (3), (3Z,4α,5β)-3-(dodec-11-ynylidene)-4-hydroxy-5-methylbutanolide (4), (3E,4β,5β)-3-(dodec-11-ynylidene)-4-hydroxy-5-methylbutanolide (5), matairesinol (7), syringaresinol (8), (+)-pinoresinol (9), salici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
1
11
1
Order By: Relevance
“…Moreover, compounds 1e9 were identified by analysis of spectroscopic data in comparison to those reported in literature as (Matlawska et al, 1994) (Kirmizibekmez et al, 2014), quercetin 3-O-a-L-rhamnopyranoside (4) (Materska et al, 2003), giffonin I (5) (Masullo et al, 2015b), kaempferol 3-O-a-Lrhamnopyranoside (6) (Ahmed et al, 1989), kaempferol 3-O-(4 00 -cis-p-coumaroyl)-a-L-rhamnopyranoside (7) (Yang et al, 2013), kaempferol 3-O-(4 00 -trans-p-coumaroyl)-a-L-rhamnopyranoside (8) (Yang et al, 2013), and alnusone (9) (Masullo et al, 2015b).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, compounds 1e9 were identified by analysis of spectroscopic data in comparison to those reported in literature as (Matlawska et al, 1994) (Kirmizibekmez et al, 2014), quercetin 3-O-a-L-rhamnopyranoside (4) (Materska et al, 2003), giffonin I (5) (Masullo et al, 2015b), kaempferol 3-O-a-Lrhamnopyranoside (6) (Ahmed et al, 1989), kaempferol 3-O-(4 00 -cis-p-coumaroyl)-a-L-rhamnopyranoside (7) (Yang et al, 2013), kaempferol 3-O-(4 00 -trans-p-coumaroyl)-a-L-rhamnopyranoside (8) (Yang et al, 2013), and alnusone (9) (Masullo et al, 2015b).…”
Section: Resultsmentioning
confidence: 99%
“…The work of Yang et al . () indicated that epicatechin isolated from the aerial part of Lindera akoensis could decrease the LPS‐stimulated NO production in RAW264.7 cell without exploring the related mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation plays an important role in the development of many diseases, and different cell types are recruited, including monocytes/macrophages, neutrophils and lymphocytes, to the tissue during the process of inflammation [ 12 , 13 , 14 ]. The LPS-stimulated murine macrophage model is a well-known system to assess the anti-inflammatory activities of marine- and terrestrial-derived secondary metabolites in vitro [ 15 , 16 , 17 , 18 ]. LPS could upregulate the production of various pro-inflammatory mediators, including cytokines, chemokines and enzymes, such as COX-2 and iNOS, which play critical roles in inflammatory processes via activation of the nuclear factor (NF)-κB signaling pathway [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%